Chat GPT Integration in English Learning: Effects on Pre-Service Primary Teachers’ Language Skills at Universitas Pasifik Morotai - Megawati Basri; Risky Richlos Sarapung (Foreign Language Instruction Probe, 2026)
English proficiency is an essential competency that university students, especially prospective teachers in the Primary School Teacher Education Program (PGSD), must possess. However, many students in underdeveloped, frontier, and outermost regions (3T), such as Universitas Pasifik Morotai, still face difficulties in mastering grammar, vocabulary, and speaking fluency. Along with technological advancements, ChatGPT, as an AI product, offers an interactive and flexible learning solution. This study aims to examine the effect of using ChatGPT on the English proficiency of PGSD students. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 30 fourth-semester PGSD students divided into two groups: an experimental group using ChatGPT and a control group receiving conventional learning. Data were collected through pre-test and post-test and analysed using an independent samples t-test. The results showed a significant difference between the two groups. The experimental group obtained an average post-test score of 46.67, higher than the control group at 40.27. The t-test result showed a t-value of 3.51 and a p-value of 0.00155 (p < 0.05), indicating that the use of ChatGPT significantly improves students' English proficiency. The conclusion is that ChatGPT is effective as a learning tool for English in higher education, especially in remote areas. The findings imply the need for integrating AI technology into language learning curricula and promoting self-directed learning